(untitled) (Human Geographies – Journal of Studies and Research in Human Geography, 2024)
In foreign countries, rural tourism is developing with a high rhythm. Kazakhstan also has excellent opportunities for the development of this type of tourism. Currently, rural tourism in Kazakhstan is not fully developed. The article deals with the issues of organising rural tourism based on agriculture in the Aktobe Region. The study aims to improve methodological approaches to rural tourism development as an innovative activity type in the context of agricultural diversification. Three methodological stages have been identified: assessing the potential for rural tourism development, identifying priority types and subtypes of rural tourism, and identifying priority and promising areas for rural tourism development. The work assessed the possibilities of rural tourism development in the districts of the Aktobe Region using the ranking method.